DAMPAK COVID-19 TERHADAP PENDAPATAN PEDAGANG DI PASAR TRANSIT PASSO - Chrismona Wakim; Josef Papilaya; Geradin Rehatta (P3M Politeknik Negeri Ambon, 2022)
This study aims to analyze the impact of the Covid-19 pandemic on the income of basic food traders in Ambon City. A case study of basic food traders at the Transit Passo market. The sample in this study was 15 basic food traders who traded in the Transit market. The data collection technique in this study was a questionnaire. The analytical technique used in this study was t test analysis. The t test used was a paired sample t test. -test), Normality test, Homogeneity test, Linearity test. The results showed that there was a significant difference in the income of basic food traders, before and after the Covid-19 pandemic, the average decrease in the income of basic food traders before and after the Covid-19 pandemic seen from the average sword income before the Covid-19 pandemic was Rp. . 7,000,000 decreased to Rp. 3,700,000 after the Covid-19 pandemic. Keywords: The impact of the Covid-19 pandemic, income of food vendors.